Particle filtering for computer vision-based identification of frame model parameters - Tekieli, Marcin; Słoński, Marek (Computer Assisted Methods in Engineering and Science; Vol 21 No 1 (2014), 2017)
In this paper we present a new approach for solving identification problems based on a novel combination of computer vision techniques, Bayesian state estimation and finite element method. Using our approach we solved two identification problems for a laboratory-scale aluminum frame. In the first problem, we recursively estimated the elastic modulus of the frame material. In the second problem, for the known elastic constant, we identified sequentially the position of a quasi-static concentrated load.